2022
DOI: 10.3389/fonc.2022.827755
|View full text |Cite
|
Sign up to set email alerts
|

High Systemic Immune Inflammation Index Is Associated With Low Skeletal Muscle Quantity in Resectable Pancreatic Ductal Adenocarcinoma

Abstract: Background and AimsFailing immune surveillance in pancreatic ductal adenocarcinoma (PDAC) is related to poor prognosis. PDAC is also characterized by its substantial alterations to patients’ body composition. Therefore, we investigated associations between the host systemic immune inflammation response and body composition in patients with resected PDAC.MethodsPatients who underwent a pancreatectomy for PDAC between 2004 and 2016 in two tertiary referral centers were included. Skeletal muscle mass quantity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
8
0
2
Order By: Relevance
“…( 11 ) in 2014, which could reflect the local immune response and systemic inflammation in the whole human body ( 12 15 ). SII has been used in past studies to predict and evaluate the prognosis of various solid tumors, such as gastric cancer ( 16 , 17 ), non-small cell lung cancer ( 18 , 19 ), pancreatic cancer ( 20 ), and esophageal cancer ( 21 , 22 ). In addition, SII also has a high value for the prognosis of cardiovascular disease ( 23 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 11 ) in 2014, which could reflect the local immune response and systemic inflammation in the whole human body ( 12 15 ). SII has been used in past studies to predict and evaluate the prognosis of various solid tumors, such as gastric cancer ( 16 , 17 ), non-small cell lung cancer ( 18 , 19 ), pancreatic cancer ( 20 ), and esophageal cancer ( 21 , 22 ). In addition, SII also has a high value for the prognosis of cardiovascular disease ( 23 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only 5 studies explored the relationship between pretreatment SMI and PFS. [ 28 , 31 , 35 , 38 , 44 ] The pooled demonstrated that lower pretreatment SMI was a risk factor of worse PFS in pancreatic carcinoma patients (HR = 1.41, 95% CI: 1.08–1.84, P = .012; I 2 = 67.1%, P = .016) (Fig. 3 ; Table 2 ).…”
Section: Resultsmentioning
confidence: 97%
“…[ 49 ] A lot of studies have indicated that skeletal muscle plays an important role in the systematic inflammation. [ 44 , 50 ] Besides, several inflammatory parameters such as the neutrophil to lymphocyte ratio, white blood cell count, C-reactive protein levels, erythrocyte sedimentation rate and systemic immune-inflammation index were found to be higher in sarcopenic patients. [ 44 , 51 ] As mentioned above, most of these inflammatory indexes have a high prognostic value in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography (CT) measured body composition, including subcutaneous and visceral fat and muscle, has been shown to be associated with systemic inflammatory immune and metabolic status. More importantly, it has been recognized as a predictor of many tumor and metabolic diseases [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%